2019
DOI: 10.3390/jmse7060171
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Analysis of a Novel Adaptively Counter-Rotating Wave Energy Converter for Powering Drifters

Abstract: Nowadays, drifters are used for a wide range of applications for researching and exploring the sea. However, the power constraint makes it difficult for their sampling intervals to be smaller, meaning that drifters cannot transmit more accurate measurement data to satellites. Furthermore, due to the power constraint, a modern Surface Velocity Program (SVP) drifter lives an average of 400 days before ceasing transmission. To overcome the power constraint of SVP drifters, this article proposes an adaptively coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
(36 reference statements)
0
7
0
Order By: Relevance
“…The blades (5) are fixed between the flywheel (9) and the blade assembly (4) and they form the blade groups. The blade groups are connected to the generator through the spindle (3), and the stabilizer wings are connected to the outside of the generator through the fixed stabilizers (8). As shown in Figure 1b, this PSU can be made in small size, which helps to integrate within the unmanned marine equipment or move with it.…”
Section: Design and Structurementioning
confidence: 99%
See 1 more Smart Citation
“…The blades (5) are fixed between the flywheel (9) and the blade assembly (4) and they form the blade groups. The blade groups are connected to the generator through the spindle (3), and the stabilizer wings are connected to the outside of the generator through the fixed stabilizers (8). As shown in Figure 1b, this PSU can be made in small size, which helps to integrate within the unmanned marine equipment or move with it.…”
Section: Design and Structurementioning
confidence: 99%
“…The WECM absorbs wave energy and converts it into heave motion (mechanical energy) for the PSU's input energy, then the PSU converts its heave motion into rotational motion to generate electricity [8,9], as shown in 0. The PSU converts wave energy into electrical energy through its unique mechanical structure and transmission mechanism.…”
Section: Working Principlementioning
confidence: 99%
“…In order to verify the working principle of the new WEC and preliminarily test its performance characteristics at the beginning of the study, we conducted a wave tank experiment on the physical prototype of WEC [48]. As shown in Figure 18, the test platform mainly includes a wave generator, a water tank, a control room, a data acquisition card (DAQ card), a test computer and other necessary circuit components.…”
Section: Experiments In Wave Tankmentioning
confidence: 99%
“…The turbine is designed in a design adapted to small speeds. It is shown that the structure of the working wheel and the angle of influence of the blades, its shape and materials are made according to scientifically based conclusions, and it can work effectively with a low-speed generator [11][12][13][14]. "The energy sector is being developed on a large scale in the Republic of Uzbekistan.…”
Section: Introductionmentioning
confidence: 99%